Three dimensions of effective mission implementation. Issue 4 (August 2018) - Rey, Carlos; Bastons, Miquel
Abstract: Mission statements are generally considered an important tool for strategy implementation. However, several authors have shown that there is a 'hole' in the mission theory, which in practice explains the inconsistency in mission statements in many companies because of the lack of motivation related to the mission. This article aims to bridge this gap by analysing the relationship between the mission of a company and its members' motivation. It entails an extension of the mission theory, in which three dimensions of mission development are analysed: formal, dynamic and motivational. On the basis of this framework, three forms of mission consistency are considered to explain the effectiveness of mission implementation: authenticity, coherence and integrity.